2013
DOI: 10.4172/2165-7556.s3-005
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Driver Ingress and Egress Using Passenger Vehicles: Considerations for Designers

Abstract: Identifying ingress and egress strategies is an important area of research in the automotive sector. Determining ingress and egress strategies can lead to safer vehicle design that reduce fall risk and improve comfort. In this systematic review, we examined studies related to ingress and egress in passenger vehicles after searching for various databases. We found 9 primary articles (of 608), all published in English. The results of the present research synthesis show that participants reported challenges with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This might be explained by the fact that a high HW tended to create a large envelope around the passenger compartment, enforcing tall participants to bend so as to get in and out of the vehicle. This statement is in accordance with the fact that a large sill width of passenger compartment may increase the risk of adverse events, especially during egress [35]. We thus concluded that a HW of 750 mm (HW3) has to be avoided.…”
Section: Influence Of Hwsupporting
confidence: 83%
“…This might be explained by the fact that a high HW tended to create a large envelope around the passenger compartment, enforcing tall participants to bend so as to get in and out of the vehicle. This statement is in accordance with the fact that a large sill width of passenger compartment may increase the risk of adverse events, especially during egress [35]. We thus concluded that a HW of 750 mm (HW3) has to be avoided.…”
Section: Influence Of Hwsupporting
confidence: 83%
“…We were also interested in examining perceptions of older drivers with mobility impairments by exploring how they managed vehicle entry and exit by joining them on routine tasks involving their automobile. Although the movements required to enter and exit a vehicle seems relatively simple, a recent systematic review of ingress and egress studies (Crizzle et al, 2014) highlighted the complexity of movements involved. As noted previously, many older drivers are injured getting into and out of a vehicle (Dellinger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The application of DHM is useful for reduction of project time-scale (Karmakar and Patel, 2014), decreased design and manufacturing cost (Berlin and Kajaks, 2010;Karmakar and Patel, 2014;Mukhopadhyay et al, 2012), lower occupational hazards (Karmakar and Patel, 2014), improved quality of products (Karmakar and Patel, 2014;Mukhopadhyay et al, 2012), increased productivity and greater efficiency (Karmakar and Patel, 2014;Mukhopadhyay et al, 2012). The DHM functions by enhancing the visualization of the interaction of a human-workstation system both in the vehicle manufacturing shop floor (Crizzle, 2013), in which it is employed to evaluate the optimal relation between safety and comfort, as well as in an agricultural shop floor (Patel et al, 2013).…”
Section: The Digital Human Modelling Technologymentioning
confidence: 99%
“…and Delmia (Berlin and Kajaks, 2010;. The computer manikins (DHM) which are algorithms specifically developed for ergonomic evaluations include Anybody Technology (Berlin and Kajaks, 2010;Bossomaier et al, 2010;Mukhopadhyay et al, 2012), 3DSSPP TM (Mukhopadhyay et al, 2012), Tecnomatic , SantosHuman (Crizzle, 2013;, HumoSim (Crizzle, 2013), HandiMan (Crizzle, 2013), Hadrian , Santos (Berlin and Kajaks, 2010; and Ergonaut (Patel et al, 2013), which is used in virtual Environment for ergonomic evaluations.…”
Section: The Digital Human Modelling Technologymentioning
confidence: 99%